The application and effects of variable duration camshaft systems to light duty diesel engines - Lancefield, T; Tim Lancefield (2002)
﻿ The work described in this thesis was carried out to investigate the application of variable valve actuation (VVA) to light-duty diesel engines for use in passenger vehicles. The background to this was that there was little published on the subject and with advanced turbochargers, exhaust gas re-circulation systems and high pressure fuel injection systems reaching maturity it seemed likely that further enhancement of the air management in this type of engine, through VVA would receive greater interest. The first section of this thesis discusses the external pressures on engine manufacturers, from legislation and from the customer expectations, which could be expected to influence the adoption of VVA, while looking at the criteria on which they would assess a VVA system prior to adoption. Section two provides an overview of the effects of VVA and how they may be used to improve engine operation by highlighting the specific features of diesel engines, i.e. cold starting and compression ratio, part load fuel economy, full load torque and transient torque rise, that can be influenced by air management and what characteristics are required from the VVA system in order to provide improvements in these areas. Having identified the key features of a VVA system that would be suitable for use in light duty diesel engines section three presents a brief literature review and discusses the family of non-constant angular velocity VVA systems that were identified as having the correct characteristics and relative simplicity necessary for any system that might be made in high volume production. This section also provides a detailed analysis of one system of this type to highlight its behaviour and impact on valve train design. Software was written to model the selected mechanism and produce the valve lift characteristics for use in simulating the engine's behaviour. Section four provides an overview of engine simulation techniques and some detail of the model constructed for this investigation. It also discusses the additional code and methodologies required to model the turbine, compressor and combustion processes, which required special treatment, and presents data to compare the behaviour of the model with the baseline of known engine behaviour. Section five presents simulation results that show the following possible improvements: a) a 23% increase in torque, b) light part-load fuel economy improvements of 13% and c) transient rise to maximum torque times reduced from 2.3 seconds to 1.6 seconds. It also discusses the features of engine operation with VVA that provide the potential for these improvements in engine operation, quantifies the benefits that might be expected at a large number of operating conditions and discusses the interactions between the VVA and other systems such as the turbo-charger and EGR system. Section six presents conclusions which beside the enumeration of the potential benefits and description of the key effects of VVA, highlights the need for test data to verify the extent to which the benefits can be realised in real engines and suggests areas for future research.